Tracing the Origin of Groundwater Nitrate in an Area Affected by Acid Rain Using Dual Isotopic Composition of Nitrate - Tianming Huang; Zhenbin Li; Baoqiang Ma; Yin Long (Geofluids)
Acid rain with a relatively high concentration of ammonium and nitrate can accelerate rock weathering. However, its impact on groundwater nitrate is uncertain. This study evaluated the dual isotopic composition of nitrate (δ15N-NO3- and δ18O-NO3-) from precipitation to groundwater in a rural mountainous area affected by acid rain. The average concentration for NH4+ is 1.25 mg/L and NO3- is 2.59 mg/L of acid rain. Groundwater NO3- concentrations ranged from <0.05 to 11.8 mg/L (baseline), and NH4+ concentrations ranged from 0.06 to 0.28 mg/L. The results show that groundwater δ18O-NO3- values (-4.7‰ to +4.2‰) were lower than the values of rainfall δ18O-NO3- (+24.9‰ to +67.3‰), suggesting that rainfall NO3- contributes little to groundwater NO3-. Groundwater δ15N-NO3- values (+0.1‰ to +7.5‰) were higher than the values of δ15N-NO3- derived from the nitrification of rainfall NH4+ (less than -4.7‰ in the study area), suggesting that nitrification of rainfall NH4+ also contributes little to groundwater NO3-. This implies that rainfall NO3- and NH4+ have been utilized. The dual isotopic composition of nitrate shows that baseline groundwater NO3- is derived mainly from nitrification of soil nitrogen. The denitrification process is limited in the groundwater system. This study shows that the rainfall NO3- and NH4+ contribute little to groundwater NO3-, improving the understanding of the nitrogen cycle in areas with a high concentration of NH4+ and NO3- in rainfall.